Analysis of determinants of financial and non-financial aspects for the fund adequacy ratio (FAR) at pension fund institutions - Dwi Asih Surjandari; Dewi Anggraeni; Yulianto Yulianto; Maria Wrightia Religiosa (The Indonesian Accounting Review, 2019)
The aim of this study is to analyze the determinants of Fund Adequacy Ratio (FAR) at Pension Fund Institutions listed in Indonesia Financial Services Authority (OJK) period 2013 - 2016. The determinants of financial aspect are proxied by financial ratio and the determinants of non-financial aspect are proxied by firm size. Sampling is done using purposive sampling method and the analysis used is SPSS version 2.0. The results of this study show that in financial aspect there are only 2 variables (the ratio of working capital / total asset and the ratio of retained earnings / total assets) that have a significant effect on FAR, while the other 4 variables consisting of the ratio of cash / total asset, the ratio of total debt / total revenue, the ratio of short-term debt / equity, and the ratio of current asset / short-term debt have no effect on FAR. In non-financial aspect, firm size also has no effect on FAR. However, all variables simultaneously have a significant effect on FAR.